Enhancing self-efficacy and Performance: an experimental comparison of psychological techniques - Wright, B. J.; O'Halloran, P. D.; Stukas, A. A. (Research Quarterly for Exercise and Sport, 2016)
Purpose: We assessed how 6 psychological performance enhancement techniques (PETs) differentially improved self-efficacy (SE) and skill performance. We also assessed whether vicarious experiences and verbal persuasion as posited sources of SE (Bandura, 1982) were supported and, further, if the effects of the 6 PETs remained after controlling for achievement motivation traits and self-esteem. Method: A within-subject design assessed each individual across 2 trials for 3 disparate PETs. A between-groups design assessed differences between PETs paired against each other for 3 similar novel tasks. Participants (N = 96) performed 2 trials of 10 attempts at each of the tasks (kick, throw, golf putt) in a counterbalanced sequence using their nondominant limb. Participants completed the Sport Orientation Questionnaire, Rosenberg Self-Esteem Scale, and General Self-Efficacy Scale and were randomly allocated to either the modeling or imagery, goal-setting or instructional self-statement, or knowledge-of-results or motivational feedback conditions aligned with each task. Results: An instructional self-statement improved performance better than imagery, modeling, goal setting, and motivational and knowledge-of-results augmented feedback. Motivational auditory feedback most improved SE. Increased SE change scores were related to increased performance difference scores on all tasks after controlling for age, sex, achievement motivation, and self-esteem. Conclusions: Some sources of SE may be more influential than others on both SE and performance improvements. We provide partial support for the sources of SE proposed by Bandura's social-cognitive theory with verbal persuasion but not vicarious experiences improving SE.